Acute effect of curcumin on interleukin-6 (IL-6) levels and C-reactive protein (CRP) levels after high-intensity physical exercises - Kusnanik, N. W.; Komaini, A.; Adi, S.; Pradana, P. Y.; Ayubi, N.; Bird, S. P. (Trends in Sport Sciences, 2024)
Around 30 million people worldwide experience pain are usually treated with NSAIDs. Providing complementary and therapeutic therapies as means of pain management would benefit those individual suffering with chronic pain. One such non-pharmacological natural compound reported to offer therapeutic application is curcumin.